2022
DOI: 10.7206/cemj.2658-0845.76
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Service Brand Passion Through Self-Congruity: The Moderating Role of Gender and Age

Abstract: Purpose: Using congruity theory, triangular theory of love, gender schema theory, and generational cohort theory, this study aimed to examine the relationships between congruity types and consumers’ service brand passion, along with the moderation effect of gender (i.e. male vs. female customers) and age (i.e. young vs. older customers) in these relationships. Design/methodology/approach: A total of N=252 valid responses were collected from the customers of service brands (e.g. bus riders), and the theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…We found that the effects of clothing congruity are different between adolescent and elderly consumers, providing insights into male consumers' apparel shopping behavior in these two specific age groups. Consistent with the findings of previous studies on the moderating effects of consumers' age, 12,34 the effect of clothing congruity on consumers' expectation of and satisfaction with salesperson's performance are stronger among elderly consumers than among adolescent consumers. Male elderly consumers have higher expectations of salesperson's performance and are more satisfied with the performance than male adolescent consumers if the salesperson wears a style of clothing similar to what the consumers prefer to wear.…”
Section: Academic Contributionssupporting
confidence: 89%
See 1 more Smart Citation
“…We found that the effects of clothing congruity are different between adolescent and elderly consumers, providing insights into male consumers' apparel shopping behavior in these two specific age groups. Consistent with the findings of previous studies on the moderating effects of consumers' age, 12,34 the effect of clothing congruity on consumers' expectation of and satisfaction with salesperson's performance are stronger among elderly consumers than among adolescent consumers. Male elderly consumers have higher expectations of salesperson's performance and are more satisfied with the performance than male adolescent consumers if the salesperson wears a style of clothing similar to what the consumers prefer to wear.…”
Section: Academic Contributionssupporting
confidence: 89%
“…Huaman-Ramirez 33 found that self-congruity causes older consumers to have more positive attitudes toward a tourist destination. Gilal et al 34 found that brand-user image congruity is more important for forming brand passion among older consumers than among younger consumers. These studies showed that consumers' age moderates the effects of self-congruity on consumers' attitudes and emotional states, and the self-congruity effect is stronger among older consumers than among younger consumers.…”
Section: Consumers' Age As a Moderation Of The Effects Of Clothing Co...mentioning
confidence: 99%
“…Similarly, another area for future research is to look into how online ads on social media (e.g., Facebook) impact customer intention to buy secondhand products when they cannot really touch the product. Likewise, there is value in investigating how various dimensions of product design (such as affective, cognitive, reflective, and ergonomic aspects) and the availability of a variety of secondhand goods impact consumer decision‐making (Bhutto et al, 2021; Gilal, Memon, et al, 2022; Gilal, Shah, et al, 2022). This investigation could focus on comparing consumer behavior in physical versus online retail environments, particularly when customers have had positive or negative prior experiences with secondhand consumption.…”
Section: Way Forward: a Research Agenda For Secondhand Consumption Ba...mentioning
confidence: 99%
“…This shall help the marketing scholars to differentiate and develop their target markets. Likewise, gender schema theory can also be used along with generational cohort theory to understand if there are any differences in the buying habits of generational cohorts (Gilal et al, 2021; Gilal, Memon, et al, 2022; Gilal, Shah, et al, 2022). We also recommend marketing scholars investigate secondhand consumption through the lens of Big Five personality traits (Barrera & Ponce, 2021).…”
Section: Way Forward: a Research Agenda For Secondhand Consumption Ba...mentioning
confidence: 99%
See 1 more Smart Citation